ROV e Strumentazione a basso costo per rilievi fotogrammetrici di siti archeologici sommersi - Costa, Elisa; Guerra, Francesco; Vernier, Paolo (Archeomatica, 2018)
ROVs have been employed to explore underwater environments and have played an important role for documentation and surveys in different fields of scientific application. The employment of a low-cost vehicle support a request for safer, cheaper and efficient methods for exploring underwater environments. The paper is related to photogrammetric surveys for the documentation of underwater environments and to comparison between different solutions: two GoPro Hero4 Session -images and videos- and a Nikon D610. Some targets have been used to connect in the same reference system the different models, allowing the comparisons of the point clouds.